EXPERIENCE OF RITUXIMAB USE IN A PATIENT WITH SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS - E. I. Alekseeva; E. V. Mitenko; T. M. Bzarova; S. I. Valieva; R. V. Denisova; T. V. Sleptsova; K. B. Isaeva; E. L. Semykina; E. G. Chistyakova; A. N. Fetisova (Педиатрическая фармакология)
The article presents a case of early onset and severe systemic form of juvenile idiopathic arthritis refractory to classical immunosuppressive therapy, including pulse therapy with methotrexate and combined therapy with methotrexate and cyclosporine. There is described the successful use of chimeric antibodies to CD20 on B lymphocytes — Rituximab — a dose of 375 mg/m2 of body surface in the form of intravenous infusions of 1 time per week for 4 weeks. The child has got one course of treatment with rituximab. By the 12th week of treatment the extraarticular disease manifestations and acute inflammatory changes in the joints stopped, the range of motion in affected joints significantly increased. 22 weeks later the drug induced the development of clinical and laboratory remission, the duration of which is 2.5 years.